2021
DOI: 10.3390/f12060806
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Ecological Value of an Urban Forest Park: A Case Study of Sinhua Forest Park in Taiwan

Abstract: Urban forests offer multiple functions: they can balance negative effects from the environment and provide the public with a place for leisure and recreation. Hence, urban forests are crucial to urban ecology and have been widely studied. In addition, relevant study results were applied for policymaking in urban development and forest park management. This study evaluated the ecological value of the Sinhua Forest Park and examined whether the socioeconomic background of participants influences their willingnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Previous studies have also demonstrated the positive impact of environmental attitudes on the value of environmental goods and services. For instance, [38,66,107] found a positive and significant effect of the NEP on people's WTP in their research. As highlighted in [47], positive environmental attitudes correlate with increased WTP for environmental protection, a trend corroborated by findings in this study.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies have also demonstrated the positive impact of environmental attitudes on the value of environmental goods and services. For instance, [38,66,107] found a positive and significant effect of the NEP on people's WTP in their research. As highlighted in [47], positive environmental attitudes correlate with increased WTP for environmental protection, a trend corroborated by findings in this study.…”
Section: Discussionmentioning
confidence: 91%
“…The NEP scale is a globally recognized survey tool crafted to gauge environmental concerns across populations using a comprehensive set of fifteen statements [64]. These statements within the NEP address attitudes toward the environment [65] and are categorized into five dimensions: acceptance of growth limits, anti-anthropocentrism, recognition of natural balance fragility, rejection of exceptionalism, and acknowledgment of a potential ecocrisis [66]. This section prompts respondents with statements reflecting either an anthropocentric or ecocentric worldview, asking them to rate their agreement from "fully disagree" to "fully agree".…”
Section: Methodsmentioning
confidence: 99%
“…Even though these objects are mostly small green spaces, their significance to the population is very high [26][27][28][29][30] especially in the era of the COVID-19 pandemic [19]. The willingness to pay by young adults for urban forestry itself is variable and depends on many factors, including, for example, the structure of the forest and small architecture, etc., [23,[31][32][33][34][35]. Determining the accuracy and reliability of the hypothetical WTP amounts reported is also significant.…”
Section: Discussionmentioning
confidence: 99%
“…The research carried out in Warsaw pocket parks is in line with this trend. However, there is no shortage of scientific reports that do not support this relationship [33][34][35]38,43,52]. This possibly comes from the fact that most often no entrance fees are charged to these types of facilities, and any costs of maintaining them are usually borne by local/municipal or state budgets.…”
Section: Discussionmentioning
confidence: 99%
“…The ecological space within a given city provides citizens with basic social functions, such as recreation and leisure [28][29][30], and important ecological service functions [31][32][33]. In the field of urban planning, ecological spatial planning and layout design more notably consider social service functions [34,35].…”
Section: Introductionmentioning
confidence: 99%